2015
DOI: 10.1371/journal.pone.0127982
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Complete Submergence of Rice at the Tillering Stage Increases Yield

Abstract: Flooding is a major threat to agricultural production. Most studies have focused on the lower water storage limit in rice fields, whereas few studies have examined the upper water storage limit. This study aimed to explore the effect of waterlogging at the rice tillering stage on rice growth and yield. The early-ripening late japonica variety Yangjing 4227 was selected for this study. The treatments included different submergence depths (submergence depth/plant height: 1/2 (waist submergence), 2/3 (neck submer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Under natural conditions, plants are frequently exposed to transient or long-term soil waterlogging, which has long been identified as a major abiotic stress [ 1 , 2 ]. Soil waterlogging significantly limits growth, development, and survival of numerous plant species, not only in natural ecosystems but also in agricultural and horticultural systems [ 3 , 4 ]. Exploring effective approaches is of urgent need to improve plant waterlogging tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Under natural conditions, plants are frequently exposed to transient or long-term soil waterlogging, which has long been identified as a major abiotic stress [ 1 , 2 ]. Soil waterlogging significantly limits growth, development, and survival of numerous plant species, not only in natural ecosystems but also in agricultural and horticultural systems [ 3 , 4 ]. Exploring effective approaches is of urgent need to improve plant waterlogging tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Similar finding was occurred in the report of Bhowmick et al (2014), in which, higher seed setting rate contributed to higher grain yield of submergence rice. In addition, filled grain percentage was affected by increase water depth and flooding duration (Zhang et al, 2015). In the present study, the treatments in which no potassium was applied (N1 and N3) adversely affected the yield and its components.…”
Section: Discussionmentioning
confidence: 48%
“…The higher the plants dry matter weight, the higher the obtained grain yield. In addition, the research result of [23] reported that the grain yield also has very real relationship to the nitrogen content.…”
Section: Discussionmentioning
confidence: 99%